Agents and Peer-to-Peer Computing 6th International Workshop, AP2PC 2007, Honululu, Hawaii, USA, May 14-18, 2007, Revised and Selected Papers - Joseph, Samuel R. H.; Despotovic, Zoran; Moro, Gianluca; Bergamaschi, Sonia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-workshop proceedings of the 6th International Workshop on Agents and Peer-to-Peer Computing, AP2PC 2007, held in Honululu, Hawaii, USA, in May 2007, in the context of the 6th International Joint Conference on Autonomous Agents and Multi-Agent Systems, AAMAS 2007. The 8 revised full papers presented together with 1 summary paper were carefully reviewed and selected from 14 initial submissions; they are fully revised to incorporate reviewers' comments and discussions at the workshop. The volume is organized in topical sections on agent and peer trust, performance and testing, grid and distributed computing, as well as location and search services.
Summary Paper -- What Agents and Peers Have to Offer Each Other: A Partial History of the AP2PC Workshop -- Agent and Peer Trust -- Information Sharing among Autonomous Agents in Referral Networks -- Performance and Testing -- Performance Prediction in Peer-to-Peer MultiAgent Networks -- P2P Agent Platform: Implementation and Testing -- Grid and Distributed Computing -- A Dynamic Pricing and Bidding Strategy for Autonomous Agents in Grids -- Agent-Based Autonomous Result Verification Mechanism in Desktop Grid Systems -- Enabling Grassroots Distributed Computing with CompTorrent -- Location and Search Services -- Design of a Secure and Decentralized Location Service for Agent Platforms -- Flexible Bloom Filters for Searching Textual Objects.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Computers and Society